Corporate Litigation, Governance, and the Role of Law Firms - FERRELL, FRANK ALLEN; MANCONI, ALBERTO; NERETINA, EKATERINA; POWLEY, WILLIAM; RENNEBOOG, LUC (Journal of Accounting Research, 2026)
ABSTRACT We study plaintiff law firms in corporate litigation, focusing on “star” firms that dominate settlement outcomes. Stars are associated with larger settlements; however, much of this effect is predicted by the defendant's litigation insurance coverage, suggesting assortative matching of stars with lawsuits that have ex ante larger expected payoffs. Moreover, stars charge higher fees for a given settlement size. Additional tests suggest that visibility and information asymmetry vis‐à‐vis less sophisticated plaintiffs help sustain the stars’ market share. These findings advance our understanding of corporate litigation and the agency relationship between plaintiff law firms and their clients.